Identification of Silencing Suppressor Protein Encoded by Strawberry Mottle Virus - Fan, Lingjiao; He, Chengyong; Gao, Dehang; Xu, Tengfei; Xing, Fei; Yan, Jiaqi; Zhan, Binhui; Li, Shifang; Wang, Hongqing (Frontiers in Plant Science, 2022)
Strawberry mottle virus (SMoV) is associated with strawberry decline disease, causing losses to fruit yield and quality. In this study, using a screening system that enables detection of both local and systemic plant host (RNA silencing) defense responses, we found that Pro2Glu and P28, encoded by SMoV RNA2 genome, functioned to suppress local and systemic RNA silencing triggered by single- but not double-stranded GFP RNA. Subcellular localization assay revealed that both Pro2Glu and P28 were localized to nucleus and cytoplasm. The deletion of 11 amino acid residues at the C-terminus destabilized Pro2Glu protein, and the disruption of two conserved GW motifs deprived Pro2Glu of ability to suppress RNA silencing. Additionally, SMoV Pro2Glu and P28 enhanced the accumulation of potato virus X (PVX) in Nicotiana benthamiana 22 days post-infiltration, and P28 exacerbated significantly the symptoms of PVX. Collectively, these data indicate that the genome of SMoV RNA2 encodes two suppressors of RNA silencing. This is the first identification of a stramovirus suppressor of RNA silencing.